EMU Journal of Urban Research and Development (JURD) Vol:1 No:1 (2020) - N/A (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
[Abstract Not Available]
The Journal of Urban Research and Development (JURD) aims to provide a discussion platform for original research on urban and planning issues, covering a wide range of disciplines contributing to issues and challenges in urban development. JURD intends to be an easily accessible resource for researchers and practitioners in the fields of urban and regional planning, urban design, landscape architecture, human geography, urban sociology, urban economics, urban infrastructure, etc. It is a unique platform for dialogue and exchange of ideas.
Keywords: Architecture - Urban Development - Urban Research - Urban and Planning; Urban Design Theory - Urban Design Education - Urban Regeneration - Urban Conservation & Revitalization - Urban Culture; Urban and Regional Planning - Urban Landscape - Urban Morphology - Urban Housing - Urban History; Urban Representations - Urban Image and Identity - Urban Public Space - Urban Policy - Urban Strategies - Urban Sustainability and Sustainable Urban Design; Urban Sociology - Urban and Environmental Psychology - Urban Economics - Urban Growth